Bauchi State agricultural Development Programme: consolidated reports 1981 (Bauchi, Nigeria, 1981)
This consolidated report of the Bauchi State Agricultural Development Programme covering the Annual report for the Year ended 31 December, 1981; Northern zone progress report; Western zone progress report; Central zone progeress report and Eastern zone progress reports
osc 22/05/2019
Arch
Keywords: Agricultural economics; Nigeria